The fundamental research on determinants of foreign direct investment: case in Malaysia / Fadhilah Mohd Ishak @ Zainudin, Asma Shazwani Shari and Wan Masnieza Wan Mustapha - Mohd Ishak @ Zainudin, Fadhilah; Shari, Asma Shazwani; Wan Mustapha, Wan Masnieza (2010)
Over the past two decades, Malaysia received substantial of foreign direct investment (FDI) in its location which is an important engine of its economic growth. Therefore, this study explores the determinants of FDI in Malaysia by focusing on three macroeconomic variables namely GDP, Exchange Rate and Development Expenditure. The reasons for choosing three variables are to narrow down the actual contributor of FDI inflows in Malaysia and to know its definite results. The analysis was done by using Statistical Package for Social Science (SPSS version 16). After going through the model adequacy checking, lag dependent variable (FDIt-1) is added as explanatory variable to overcome the problem of autocorrelation. The result of the corrected model shows that GDP and lag dependent variable are significantly influenced inflow of FDI to Malaysia and the relationships are positive while the exchange rate is not significant in explaining the determinants of FDI in Malaysia. Meanwhile, development expenditure is dropped because of the multicollinearity problem.